Rare case of a patient with symptomatic Meckel's diverticulum enteroliths. Issue 2 (19th February 2021) - Callan, Rory; Assaf, Nazrin; Shaikh, Muhammad Imtiaz; Chattopadhyay, Dipankar
Abstract : A 61-year-old man presented with non-specific abdominal symptoms, including left groin pain and change in bowel habits. Investigations revealed a cystic lesion, containing numerous irregular calcifications, with the primary differential being a dermoid cyst containing teeth-like calcifications. At laparoscopy it was found to be a Meckel's diverticulum, containing a large number of enteroliths. This case revealed the importance of considering enteroliths in patients with imaging showing intra-abdominal calcifications, and laparoscopy for diagnosis and treatment.